ISLAMIC PHILOSOPHY: A COMPARATIVE PERSPECTIVE BETWEEN IBNU KHALDUN AND KARL MARX - Syam, Abdi Mubarak; Dalimunthe, Maulana Andinata; Suhendar, Aris; Rambe, Rahmansyah Fadlul Al Karim (SYAHADAT: Journal of Islamic Studies, 2024)
The formation of history is more than just recording past events. More than that, history can illuminate human development. Because history is the chronological development of humanity. Ibn Khaldūn and Karl Marx are two influential philosophers who have discussed human civilization. Ibn Khaldūn, a medieval philosopher, focused on the unity of the people, while Karl Marx, a modern philosopher, examined historical change through the lens of class (the caste that plays a role in historical change). This research aims to analyze historical change, or what the pair represents. The author uses primary sources, including Ibn Khaldūn' s Muqaddimah and Karl Marx: Selected Writings, to collect relevant data. Thereafter, the study utilized desk research with descriptive, analytical, and interpretative methods. This research proposes the same method to discuss Islamic philosophy in history between Ibn Khaldūn and Karl Marx, although it is not necessarily the same. Ibn Khaldūn's historical research reflects the perspective of the classical period, while Karl Marx's reflects the modern situation. In their theories, both Ibn Khaldūn and Karl Marx emphasized community, including the state, society, and bonds ('ashābiyyah) as the roots of the growth of the philosophy of history. Both theories present the philosophy of history in a similar way, although there are differences.